EW Early Warning Indicator Krisis Nilai Tukar Pada Perekonomian Indonesia - Anto Kurniawan; Nurbetty Herlina Sitorus (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2018)
The purposes of this study to analyze the influence of the Early Warning Indicator based on the external sector: Real Effective Exchange Rate, Growth Export and Growth Import of the currency crisis in Indonesia. In determining the currency crisis, will be calculated EMP (Exchange Market Pressure). This study used time series data for 2000:Q1-2015:Q4 period, using multiple regression with Error Correction Model (ECM) method. The result of the study shows that the Real Effective Exchange Rate has negative effect, Growth Export has negatif effect and Growth Import has positive effect towards currency crisis in Indonesia